A GAME THEORETIC APPROACH FOR THE OPTIMAL INVESTMENT DECISIONS OF GREEN INNOVATION IN A MANUFACTURER-RETAILER SUPPLY CHAIN - Xi, Sha; Lee, Chulung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
This paper analyzes a single manufacturer, single retailer supply chain involving green innovation investment. Consumer demand is dependent on selling price and greening effort of both the manufacturer and the retailer. We consider the effects of consumer environmental awareness, perception difficulty of green products, and degree of goods’ necessity on decision making. According to the relationship between the manufacturer and the retailer, three non-coordinated game (including Manufacturer-Stackelberg, Retailer-Stackelberg, and Vertical Nash) and one coordinated supply chain structures are proposed. The pricing and green investment policies are investigated under these four supply chain structures, respectively. A Retail Fixed Markup (RFM) policy is analyzed when channel members fail to achieve supply chain coordination. The effects of RFM on supply chain performance are evaluated. We compare optimal solutions and profits under the coordination, the Manufacturer-Stackelberg, and the RFM supply chain structure numerically and provide managerial insights for practitioners.